A Preliminary Study on Colour Recognizer for Visually Disabled People - Wahid, M.A.; Ahmad, M.Y.; Md.Zain, M.Z.; Saad, S.M.; Hussein, M.; Ahmad, Z. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Nowadays, visually disabled people face difficulties to match the colour of everyday life. This comprises activity to find the colour of cloth, the colour of food and surrounding items near them. Before this, there are many methods developed to solve this problem like braille sticker with colour code embedded, human assisting and a device that can produce audio output from colour sensor data called colour recogniser. This paper presented a preliminary study on colour recogniser for visually impaired people. The colour recogniser consists of three components; microcontroller, a colour sensor and a pair of speaker. The colour sensor will read the colour of desired surface or object and send reading values to the microcontroller. The microcontroller will process the information and displayed the colour audio output through the speaker based on the recognised colour. The device is powered by dry cell batteries and also lightweight. It is designed to be user-friendly, practical and also easy to carry everywhere. To ensure the device is working correctly in determining the type of colour detected, an experiment to validate the device was performed with 12 standard colours. The result shows that validation of the colour recogniser has proved the ability of the colour recogniser. This device will be useful for visually disabled people and can help them to solve their difficulties to match the colour for everyday life.